Suppressor Effects of Positive and Negative Religious Coping on Academic Burnout Among Korean Middle School Students - Noh, Hyunkyung (Journal of religion and health, 2016)
Statistical suppressor effects in prediction models can provide evidence of the interdependent relationship of independent variables. In this study, the suppressor effects of positive and negative religious coping on academic burnout were examined using longitudinal data. First, 388 middle school students reported their type of religion and use of positive and negative religious coping strategies. Four months later, they also reported their level of academic burnout. From structural equation modeling, significant suppressor effects were found among religious students. That is, the coefficients became larger when both positive and negative religious coping predicted academic burnout simultaneously, compared to when each religious coping predicted academic burnout alone. However, suppressor effects were not found among non-religious students.